Is the OECD model suitable for strategic public enterprises in terms of national development? : reflections from CODELCO case, Chile - Francisco Casta\~neda; Diego Barría; Germán Astorga (Is the OECD model suitable for strategic public enterprises in terms of national development? : reflections from CODELCO case, Chile, 2015)
This academic work address about the Chilean state owned company (CODELCO) and how it deals with the recommendations of OECD in order to define determined corporate governance. The core of this work is based on establishing a critic analysis to these guidelines. In the last decades, state owned companies (SOEs) have returned to play a visible role in world economies. The privatization wave experienced by the world, with different intensities depending on the region since the 1970s, was not successful and weakened the extent of intervention of SOEs across economics. Large enterprises survived and in recent years, for example in Latin America, a new phenomenon has emerged: the renationalisation of enterprises previously privatized. This is even evident in economies like Chile, in which between 1970s and 1990s, many of the then SOEs were privatized. Enterprises that remain in the hands of the Chilean State have been managed, increasingly, under a total private logic, inspired by notions of corporate governance of the OECD. However, a SOE, CODELCO (National Copper Corporation of Chile), one of the largest state-owned copper enterprises in the world, has not fully entered into that scheme. Both the Pinochet dictatorship (1973-1990) and the later democratic governments have considered CODELCO as strategic, due to its contribution to the national budget.
2575017-3; 635679337